Moderate versus intensive treatment of hypertension using amlodipine/valsartan and with the addition of hydrochlorothiazide for patients uncontrolled on angiotensin receptor blocker monotherapy: results in racial/ethnic subgroups - Ofili, Elizabeth O., MD, MPH, FACC; Oparil, Suzanne, MD; Giles, Thomas, MD; Pitt, Bertram, MD; Purkayastha, Das, PhD; Hilkert, Robert, MD; Samuel, Rita, MD; Sowers, James R., MD (Journal of the American Society of Hypertension, 2011)
Abstract Combination therapy may reduce racial/ethnic differences in response to antihypertensives. In this post-hoc analysis, we evaluated treatment response by race/ethnicity among hypertensive adults enrolled in a 12-week, double-blind study in which patients previously uncontrolled (mean sitting systolic blood pressure [MSSBP] ≥150 and <200 mm Hg) on angiotensin receptor blocker (ARB) monotherapy (other than valsartan) for 28 days or more (n = 728) were randomized to amlodipine/valsartan 10/320 mg (intensive) or 5/160 mg (moderate). Treatment-naïve patients (in previous 28 days) or those who failed on a non-ARB first underwent a 28-day run-in period with olmesartan 20 mg or 40 mg, respectively. Hydrochlorothiazide (HCTZ) 12.5 mg was added to both arms at week 4; optional up-titration to 25 mg at week 8 (if MSSBP >140 mm Hg). Intensive treatment provided greater BP lowering versus moderate treatment throughout the study, regardless of race/ethnicity (474 white, 198 African American, 165 Hispanic individuals). Least-square mean reductions from baseline to week 4 in MSSBP (primary outcome) ranged from 20.4 to 23.5 mm Hg (intensive) versus 17.5 to 19.0 mm Hg (moderate), across racial/ethnic subgroups. Both regimens were well tolerated. Amlodipine/valsartan/HCTZ combination therapy was efficacious across racial/ethnic subgroups. Maximal efficacy was obtained with intensive treatment.